Nigeria : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
The overarching policy challenge facing Nigeria is to reduce widespread poverty and unemployment. Macroeconomic performance was broadly positive, underpinned by buoyant international oil prices and prudent fiscal and monetary policies. The fiscal targets and the medium-term fiscal consolidation plan are consistent with supporting macroeconomic stability and creating fiscal space for much needed additional investment and social spending. Non-oil revenues need to be mobilized by moving quickly to improve tax administration in line with technical assistance (TA) recommendations. Planned structural reforms can substantially boost prospects for inclusive growth.